Advancements in Molecular Engineering: Innovations at the Nexus of Chemistry and Technology - Neha Sahu; Rizwan Arif (International Journal of Advance in Molecular Engineering, 2024)
Molecular engineering, a frontier of chemistry, merges precision and innovation to design and assemble molecular structures with unprecedented control. This abstract explores recent advances, highlighting key breakthroughs and their transformative impacts. Starting with its roots in chemical synthesis and materials science, it traces the evolution towards rational design driven by computational tools and advanced characterization techniques, enabling tailored molecular architectures. A focal point is programmable molecules, where DNA nanotechnology principles create intricate assemblies with dynamic behaviors and programmable functions. This includes advancements in molecular robotics and responsive materials, mimicking biological systems for novel applications. Additionally, the intersection of molecular engineering with quantum chemistry and machine learning unlocks new pathways for predicting and optimizing molecular properties, accelerating the discovery of novel materials and catalysts for energy, healthcare, and environmental applications. Synthetic biology has expanded through molecular engineering, exemplified by synthetic enzymes and biosensors. These engineered components offer versatile platforms for biotechnology and biomedicine, revolutionizing drug discovery and diagnostics. The abstract also addresses challenges and future directions, emphasizing the need for interdisciplinary collaboration and ethical considerations.
Keywords: Computational models; Machine Learning Algorithms; Molecular dynamics simulations; drug-receptor interactions; molecular interactions; quantum mechanics/molecular mechanics (QM/MM)